WHERE SLOITUDE RESIDES: A PRAGMATIC – STYLISTIC ANALYSIS OF JOSEPH CONRAD’S THE LAGOON - SAMIR AL-SHEIKH; ABDUL KAREEM LAZIM ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Though distinct in certain aspects, pragmatics and stylistics are two interrelated interdisciplinary fields whose main concern is the quest for meaning-making in language. Being forms of meaning, metaphorical modes can be analyzed from pragmatic- stylistic stance. If stylistics is mainly concerned with linguistic interpretation of literary discourses, pragmatics unravels the contribution of the context to the construction of meaning proper. The interaction between these subfields of linguistics has led to the emergence of the hybrid term Pragmatic Stylistics.Therefore, the term Pragmatic Stylistics has been circulated in the sphere of linguistics to state the pragmatic dimension in the deconstruction of the imaginatively works of art. The study aims at investigating speech acts, with much stress on the metaphorical modes of meaning in Joseph Conrad’s The Lagoon, and how these sequences of speech act build up the narrative image of the world. The study hypothesizes that the narrative structure of the metaphorical modes in the short story are not merely a combinatory set of syntactic structures.Rather, they are the transmitters of human experience in forms of sequential speech acts